New Insights Into the Role of β-NGF/TrKA System in the Endometrium of Alpacas During Early Pregnancy - Barraza, Daniela E.; Sari, Luciana M.; Apichela, Silvana A.; Ratto, Marcelo H.; Argañaraz, Martin E. (Frontiers in Veterinary Science, 2021)
One striking reproductive feature in South American camelids is that more than 90% of gestations are established in the left uterine horn (LUH). This phenomenon could be related to a differential vascular irrigation of the LUH. An increase of vascularization in llama endometrium was observed after systemic administration of Beta Nerve Growth Factor (β-NGF), a neurotrophin present in the uterus and placenta of various mammals that is involved in pregnancy development. We hypothesized that the β-NGF signaling pathway is related to embryo implantation in the LUH in camelids. The aim of this study was to characterize the spatial expression of β-NGF and its high-affinity receptor, TrKA, between LUH and right uterine horn (RUH) of non-pregnant (NP) and early pregnant alpacas (15 and 30 days of gestation, 15P and 30P respectively). In addition, β-NGF, TrKA, and Vascular Endothelium Growth Factor A (VEGFA) temporal gene expression patterns and counting of blood vessels were evaluated among groups. The β-NGF and TrKA were localized in the luminal, glandular, and vascular epithelium of the alpaca uterus and in the embryonic membranes of the 30-days-old conceptus. β-NGF and TrKA immunosignal were stronger in 15P females than that of NP and 30P. In addition, TrKA signal was higher in the LUH luminal epithelium of NP and 15P alpacas than that of NP-RUH and 15P-RUH. β-NGF mRNA relative abundance was higher in the 30P-RUH than that of NP-RUH; whereas TrKA mRNA abundance only differed between 15P-RUH and NP-LUH. VEGFA mRNA relative abundance was higher in NP females compared to the LUH of 15P and 30P alpacas, and lower to their right counterparts. The number of vessels per field was higher in 15P than that of 30P. A positive correlation was observed between the number of vessels per field and β-NGF immunosignal in 15P-LUH. In contrast, the area occupied by vessels was higher in 30P alpacas than of NP and 15P females. The changes of β-NGF/TrKA expression pattern in the peri-implantation endometria between LUH and RUH and their localization in the extraembryonic membranes support the implication of the neurotrophin during implantation and pregnancy development in South American Camelids.